PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2011 - Sri Wijayanti; Siti Mutmainah (Diponegoro Journal of Accounting, 2012)
This study describes the relationship between corporate governance with financial performance on banking companies. The indicator used to explain corporate governance in this study consisted of the size of the board of directors, activities (meetings) the board of commissioners, institutional ownership, the proportion of independent commissioners, the number and size of the company's audit committee, and the size of the banking companies. The method of analysis used in this study is multiple regression, because in accordance with the purpose of this study was to analyze the influence of independent variables on the dependent variables. Samples used in this study were all banking companies listed on the Indonesia Stock Exchange (BEI) in the period 2009-2011. To determine the selection of the sample used purposive sampling method. By using this method the company are obtained 19 banking companies that will be serve as samples in this study. From the results of hypothesis testing in this study, it shows that the size of the board of directors, the activity of (meeting) the board of commissioners, proportion of independent commissioners, and the audit committee is negative effect and not significantly effect on the financial performance of banking companies. The results of this study also showed that institutional ownership is positive effect but not significantly effect on the financial performance of banking companies, and firm size have a positive effect and significantly effect on the financial performance of banking companies. Overall results show that corporate governance is less effect on the performance of the banking companies.